Some aspects of the Ecology, behaviour and Vectorial capacity of the TseTse fly glossina austeni Newstead. - Owaga, M.L.a. (Kenyatta University, 1992)
A study was undertaken in the south coast of Kenya, on the tsetse fly species, Glossina austeni Newstead. The objective was to investigate its population ecology, behaviour and vectorial capacity. The main aspects studied were: habitat requirements and density, responses to sampling devices and methods, such as traps and odours, activity pattern, and infection with trypanosome parasites. Some aspects of the study, such as sampling and activity experiments, evaluation of density, dispersal and habitat requirements, and trypanosome infection rates, were conducted in the field. Others, such as assessment of the effect of temperature and relative humidity on activity and response to odours, and evaluation of the efficiency of G. austeni in picking up trypanosome parasites from infective blood meals, and in transmitting them to the next mammalian host, were conducted in the laboratory. Sampling was carried out using five trap-types, the biconical, the NG2B, the Lancia (original), Lancia (modified) and the 4t traps, to determine whether G. austeni could be trapped in sufficient numbers, and which trap might be most suitable for routine sampling. Similarly, five odour sources were tested as baits: buffalo urine, cow urine, acetone, urine derived phenols and dry ice. Period of activity, and activity pattern as related to feeding, were determined by continuous trapping, using traps and stationary vehicle, and by laboratory observation in a flight chamber, where only olfactory, but no visual stimulant, was presented to too flies. To study the density and dispersal ofG. austeni, the method of markrelease-recapture was used. By this method a sample of tsetse flies was captured, marked with artist's oil paint, fed and released to mix with the wild population. Afterwards, several samples were taken in traps, and among the flies captured were some of the marked individuals. The locations and dates where the marked flies were captured were noted for the evaluation of dispersal. The density was later assessed using the recapture figures. The interaction between G. austeni and trypanosome parasites was studied by the determination of trypanosome infection rates in the field, and the efficiency with which the fly picks up trypanosome parasites from infective blood meals and transmits them to the next host, in the laboratory. These two aspects of the vector-parasite interaction constituted the vectorial capacity of G. austeni. The results of the study show that G. austeni occur in relatively low densities in the Muhaka area of the south coast (Kenya), compared to a related but more wide-spread species G. pallidipes. Furthermore, the study showed that G. austeni was a resident species that did not disperse widely. It showed preference for forest and dense thicket. The evidence was that traps set on the forest floor consistently captured significantly more flies than those set on the fringes of the forest, or in open woodland. The effects of the different odour sources in attracting G. austeni to traps were generally poor, except those of dry ice and buffalo urine that increased the catches significantly (P<O.05). This poor response to odours was explained by the physical conditions prevailing at the coast, especially constant high relative humidities. The Lancia trap was found to be the most suitable for sampling G. austeni, but the other three types used also worked moderately well. The species was shown to be day-active, and a period of very low activity around midday. As regards ~torial capacity, the evidence showed that G. could be )ortant vector of trypanosome parasites. The rates ofinfection wild flies were higher than in two other species that ically co-exist with it in that area, namely, G. and G. In the laboratory, about of the flies tested picked up from infective blood meals, but transmission from those nature infections was i.e. all of them transmitted to the iost they fed on. However, about 50% of young (teneral) flies lad the in